(3QSGdI aj GdJhMjOs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Pj GdLdGd hGdEcQGe GYde Cfj CYJbO eYQaI Gddg JYGdi hGdJhMjO hCbhd (B: (3Ef Gddg JYGdi hGMO aQO bOje CRdj hCfg UeO dG TQjc dg hdG eKd dg hdG THjg dg hdG Tc dg hdG VO dg hdG fO dg de jRd CMOG UeOG aQOG hfRG hdG jRGd cPdc CHOGs
(3BNQgG (B:s
(3aUd (B: (3bGd Cgd GdfLhe GdTeS hGdbeQ hGdfLhe aj GdSeGA GdQGHYI bdfG aj GdSeGA GdOfjG jOd Ydjg bhdg JYGid (B: (3hdbO RjfG GdSeGA GdOfjG HRjfI GdchGcH hbGd JYGdi (B: (3hdbO RjfG GdSeGA GdOfjG HeUGHjM , hcPdc aj bUI Pj GdbQfjf (B: (3MJi EPG HdZ eZQH GdTej hLOgG JZQH aj Yjf MeFI hgh de jHdZ Edi GdSeGA GdQGHYIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds